COMPLEMENTARY NATURE OF SCIENCE AND RELIGION - Ferrao, Filipe Neri (Journal of Dharma, 2011)
As the local archbishop, I have been given the task of delivering theinaugural Address at this august gathering of people of science and ofreligion, who have converged to debate on a topic of never-diminishingrelevance: Catholicism in the World of Science.'